The child in ICC proceedings / Helen Beckmann-Hamzei. - Beckmann-Hamzei, Helen, 1980- (School of Human Rights Research series, 2015)
International law and state practice mirrors the recognition of children's particular need for protection during peacetime, but in situations in which international crimes are being committed the prosecution of international crimes committed against children before international courts and tribunals is also well embedded. While international prosecutions are thus in line with the overall development of protecting children from the consequences of armed conflict and large scale violence, the involvement of the child in international criminal proceedings also gives rise to new questions which relate to the procedural involvement of the child.As child participation in the proceedings before the International Criminal Court (ICC) constitutes a matter of fact, one may raise the question whether such participation is a welcome development. This study examines the procedural implications of child participation and thereby intends to contribute legal views and perspectives to the underlying debate on the adequacy of child participation in ICC proceedings. The study concludes with ten recommendations that underline the call.